An ace up their sleeve: a transcriptomic approach exposes the AceI efflux protein of Acinetobacter baumannii and reveals the drug efflux potential hidden in many microbial pathogens - Hassan, Karl A.; Elbourne, Liam D.; Li, Liping; Hewawasam Gamage, Hasinika K.; Liu, Qi; Jackson, Scott M.; Sharples, David; Kolstø, Anne-Brit; Henderson, Peter J.; Paulsen, Ian T. (Frontiers in Microbiology, 2015)
The era of antibiotics as a cure-all for bacterial infections appears to be coming to an end. The emergence of multidrug resistance in many hospital-associated pathogens has resulted in “superbugs” that are effectively untreatable. Multidrug efflux pumps are well known mediators of bacterial drug resistance. Genome sequencing efforts have highlighted an abundance of putative efflux pump genes in bacteria. However, it is not clear how many of these pumps play a role in antimicrobial resistance. Several studies have demonstrated that efflux pump genes that participate in drug resistance are typically under tight regulatory control and expressed only in response to their substrates. Consequently, changes in gene expression following antimicrobial shock treatments may be used to identify efflux pumps that mediate antimicrobial resistance, informing targeted functional analyses of these proteins. Using this approach we have characterised novel efflux pumps in both Gram-negative and Gram-positive bacteria. Notably, we recently applied this strategy to characterise the AceI efflux pump from Acinetobacter. AceI is a prototype for a new family of multidrug efflux proteins that is conserved across many proteobacterial lineages. Different efflux pumps in this family have been shown to confer resistance to biocides including chlorhexidine, dequalinium, benzalkonium, proflavine and/or acriflavine. The discovery of this novel family of multidrug efflux proteins raises the possibility that additional undiscovered intrinsic resistance proteins may be encoded in the core genomes of pathogenic bacteria.